MOST USED INTERACTIVE WHITEBOARDS SYSTEMS IN SLOVAKIA AND BOHEMIA - BREČKA, Peter; KOPRDA, Štefan; MAROŠ, Milan (Trends in education, 2009)
The article refers to the problemacy of the most used interactive whiteboards systems in Slovakia and Bohemia as well as to their advantages and disadvantages.
Keywords: interactive whiteboard; electronic pen; principle of functioning.